Effect of maternity waiting homes use on maternal and perinatal birth outcomes and its challenges in Amhara region, Northwest Ethiopia - Molla, Muluye; Tesfa, Mulugeta; Alle, Atsede; Molla, Firehiwot; Aschale, Abiot; Endalew, Bekalu; Gietaneh, Wodaje (Frontiers in Global Women's Health, 2023)
Abstract Background: Women’s death due to complications of pregnancy and childbirth is still high. Maternity waiting home is one of the strategies to reduce it. However, there is limited evidence on the effect of using maternity waiting homes on birth outcomes, particularly in this study area. In addition, in previous studies, the propensity score matching method was not used to evaluate the effect of maternity homes. Therefore, this study was aimed to estimate the effect of staying in maternity waiting homes on maternal and perinatal birth outcomes and its challenges in the Amhara region, Northwest Ethiopia 2018. Methods: - Institutional-based comparative cross-sectional study using both quantitative and qualitative approaches was conducted. Data were collected using structured questionnaire interviews and chart reviews. Propensity score matching analysis was used to estimate the effect of maternity waiting for a home on birth outcomes. Propensity score matching analysis was used to match potential differences in background characteristics that affect pregnancy outcomes between comparison groups. We used thematic analysis for qualitative data. Result: - A total of 548 pregnant mothers (274 stayed in maternity waiting homes and 274 did not stay) took part in this study. The proportion of adverse birth outcomes of mothers who stayed in maternity waiting homes was 15(5.5%) which is lower than those who didn’t stay 35 (12.8%). After matching by propensity score, mean adverse maternal birth outcome, the difference between didn't use maternity waiting home and used was 10.4%, at (t=3.78) at 5% level of significance. Similarly, the mean adverse perinatal birth outcome difference between mothers who didn't use MWH and used was 11% (t=4.33). Conclusions: maternity waiting home showed a significant positive effect on birth outcome. Mothers who stayed in the maternity waiting homes had low adverse maternal and perinatal birth outcomes compared to none users. Accommodations and quality health care services were the challenges mothers faced during their stay in the maternity waiting homes. Therefore, all concerned bodies should give attention accordingly to Maternity Waiting Home Service to reduce adverse birth outcomes through the strengthening of the quality of health care provided.